Pentingnya pendidikan karakter dan pengawasan terhadap lingkungan pergaulan anak sejak usia dini - Izzaini, Muhammad Fadhil (Maliki Interdisciplinary Journal, 2023)
Character education for a child is something important, because character will affect a person in his decision making, character formation is influenced by several factors, such as genetic factors, social factors, environmental factors and parental factors. Character building must be done from an early age, because at that time the child's brain is developing rapidly and is easy to be directed by parents, so parents have an important role in character building, parents must provide good character education. In addition to parents, the environment where they hang out can also affect the formation of their character, the environment has an indirect role in character building. A bad environment, as well as the wrong association with friends with bad character are the causes of damage to the child's character, which can cause the child to fall into promiscuity, so parental supervision is needed to prevent this from happening.